A brief account on enzyme mining using metagenomic approach - Patel, Tithi; Chaudhari, Hiral G.; Prajapati, Vimalkumar; Patel, Swati; Mehta, Vaibhavkumar; Soni, Niti (Frontiers in Systems Biology, 2022)
Metagenomics is an approach for directly analyzing the genomes of microbial communities in the environment. The use of metagenomics to investigate novel enzymes is critical because it allows researchers to acquire data on microbial diversity, with a 99% success rate, and different kinds of genes encode an enzyme that has yet to be found. Basic metagenomic approaches have been created and are widely used in numerous studies. To promote the success of the advance research, researchers, particularly young researchers, must have a fundamental understanding of metagenomics. As a result, this review was conducted to provide a thorough insight grasp of metagenomics. It also covers the application and fundamental methods of metagenomics in the discovery of novel enzymes, focusing on recent studies. Moreover, the significance of novel biocatalysts anticipated from varied microbial metagenomes and their relevance to future research for novel industrial applications, the ramifications of Next-Generation Sequencing (NGS), sophisticated bio-informatic techniques, and the prospects of the metagenomic approaches are discussed. The current study additionally explores metagenomic research on enzyme exploration, specifically for key enzymes like lipase, protease, and cellulase of microbial origin.